If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5x + 28 = 12x + -56 Reorder the terms: 28 + 5x = 12x + -56 Reorder the terms: 28 + 5x = -56 + 12x Solving 28 + 5x = -56 + 12x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-12x' to each side of the equation. 28 + 5x + -12x = -56 + 12x + -12x Combine like terms: 5x + -12x = -7x 28 + -7x = -56 + 12x + -12x Combine like terms: 12x + -12x = 0 28 + -7x = -56 + 0 28 + -7x = -56 Add '-28' to each side of the equation. 28 + -28 + -7x = -56 + -28 Combine like terms: 28 + -28 = 0 0 + -7x = -56 + -28 -7x = -56 + -28 Combine like terms: -56 + -28 = -84 -7x = -84 Divide each side by '-7'. x = 12 Simplifying x = 12
| 5x+28=12-56 | | 3(4+y)=2(y-6) | | 6x=7.5 | | 3x-4(-8-3x)=4 | | -x=-100 | | -3(5y-5)+2(2y+6)= | | 8x-8=7x+7 | | -2x-5=-17 | | -9x+6y=1 | | 3y-9=4y | | 7(x+1)-(6-4x)=10x | | -7x+7x+6x= | | m-2m-3m+4= | | g^3+3g^2-1g-3=0 | | -3p+40=-2p-10 | | -3p+40=-2-10 | | 8*16-2y=90 | | 7x+14=9x+18 | | -(3y+5)-(-2y-6)=0 | | 16=3(3x) | | 3(x+2)=2(x-1) | | 3x^2-30x+3=0 | | 9-5(x-2)=22 | | 4a^2=100 | | -(4y+4)-(-3y-5)=-4 | | -5+x=-15 | | 0.16(6)+0.04x=0.08(18+x) | | 0.16(6)+0.04x=(18+x) | | X-10=-5 | | 16y+8y-11y=91 | | 6c+4=22 | | 3x-16=1-2x |